Video Instructional Strategy on Biology Student’s Academic Performance in Port Harcourt, Nigeria - Umunnakwe Bernadine Akuoma; Isa Mohammed Juliana (Britain International for Academic Research (BIAR) Publisher, 2021)
The study investigated the efficacy of Video Instruction as a teaching strategy on Senior Secondary Schools Biology Students’ academic performance in Port Harcourt, Rivers State. The study adopted pretest, post-test, control group quasi–experimental design. Two Intact classes were taught using video instructional strategy as experimental group and another two classes taught using Instructional Diagrams as control group. Two research questions and two hypotheses were formulated to guide the study. Biology Performance Test on Genetics (BPTG) with 25 Objective items was developed and validated. Pilot test was carried out with reliability coefficient of 0.76 obtained, before using it for data collection. The instrument was administered as pre-test and latter reshuffled and administered as post-test. The data were analyzed using mean and standard deviation to answer the research questions while ANCOVA was used to test the hypotheses at 0.05 level of significance. The result revealed that the experimental group obtained higher mean performance score and no significant difference existed between location and academic performance. It is therefore, recommended that teachers should use video instructional strategy in the teaching and learning of sciences as it promotes internalization of abstract concepts.